Analysis of Initial Impoundment Using the F.J. Mock Flow Discharge Model at Pamukkulu Dam - Nugraha, Hendy Adiyat; Wulandari, Dyah Ari; Suharyanto, Suharyanto (TEKNIK, 2025)
The construction of a dam consists of several stages, including construction preparation, construction planning, construction execution, and initial reservoir impoundment. This study aims to determine the duration of the initial impoundment of the Pamukkulu Reservoir during dry, normal, and wet years using the F.J. Mock water availability method. Water losses in this study include reservoir water release through the bottom outlet to meet irrigation water demand at a rate of 0.3 m³/s and reservoir evaporation. The calculation of the impoundment duration is based on the monthly accumulation of volume until reaching the total storage volume of 82.57 million m³ at a normal water level elevation of +126.00 meters. The analysis results indicate that the duration of the initial impoundment of the Pamukkulu Reservoir is 11.16 months (335 days) in a dry year with an inflow reliability of 31.81%, 8.66 months (260 days) in a normal year with an inflow reliability of 63.63%, and 7.63 months (229 days) in a wet year with an inflow reliability of 77.27%. The study concludes that the Pamukkulu Dam will reach its normal water level storage volume in December (first period) during a wet year classification.